The Small GTPase Cdc42 Negatively Regulates the Formation of Neutrophil Extracellular Traps by Engaging Mitochondria - Tackenberg, Heidi; Möller, Sonja; Filippi, Marie-Dominique; Laskay, Tamás (Frontiers in Immunology, 2021)
Neutrophil granulocytes represent the first line of defence against invading pathogens. In addition to the production of Reactive Oxygen Species, degranulation and phagocytosis, these specialized cells are able to extrude Neutrophil Extracellular Traps. Extensive work was done to elucidate the mechanism of this special form of cell death. However, the exact mechanisms are still not fully uncovered. Here we demonstrate that the small GTPase Cdc42 is a negative regulator of NET formation in primary human and murine neutrophils. We present a functional role for Cdc42 activity in NET formation that differs from the already described NETosis pathways. We show that Cdc42 deficiency induces NETs independent of the NADPH-oxidase but dependent on protein kinase C. Furthermore, we demonstrate that Cdc42 deficiency induces NETosis through activation of SK-channels and that mitochondria play a crucial role in this process. Our data therefore suggests a mechanistic role for Cdc42 activity in primary human neutrophils, and identify Cdc42 activity as a target to modulate the formation of Neutrophil Extracellular Traps.